A Study on Organizational Commitment in Public Sector (International Journal of Scientific Research and Management (IJSRM), 2017)
Organizational commitment is an important factor for every organization to attain the goals and objectives of particular concern. To considering the variables of organization commitment leads to emotionally attached and loyalty based on their organization toward the employees. Objectives of the study to know the education of the respondents influencing on organizational commitment factors. The findings show that they significantly differ with factors of organizational commitment. It predicts that employees accept the policy of the organization and doing the work with very promptly to attain the goals of the organization